Respons Bibit Kelapa Sawit terhadap Berbagai Jenis Bokashi dan Pupuk NPK pada Fase Pre-nursery - Ridi, Egidius Erido; Sasli, Iwan; Ramadhan, Tris Haris (Politeknik Negeri Lampung, 2025)
Improving the quality of PMK soil by applying bokashi and NPK fertilizer is expected to increase the physical and chemical fertility of the soil. This research aims to determine the effect of bokashi and NPK fertilizer and their interaction in improving the growth of oil palm seedlings in PMK soil during the pre-nursery phase. The experiment was conducted in Ensalang Village, Sekadau Hilir District, Sekadau Regency, from October to December 2023. The experiment was arranged using a randomized complete block design (CRD) factorial with two factors. The experiment was repeated 3 times and consisted of 9 samples so that 405 experimental units were obtained. The results showed that the interaction between bokashi and NPK fertilizer affected plant height, dry weight, stem diameter, and root volume. Bokashi independently affects leaf area, plant dry weight, stem diameter, and root volume. NPK fertilizer independently affects plant height, leaf area, and plant dry weight.